(x+5)(x+6) equals x^2 +11x+30
572 Because 2x11=22 and 13x2=26 and 22x26=572.
2x2 + 11x + 15 = (x + 3)(2x + 5).
x = 8
23
(x+5)(x+6) equals x^2 +11x+30
572 Because 2x11=22 and 13x2=26 and 22x26=572.
2x2 + 11x + 15 = (x + 3)(2x + 5).
11x = 8x-6.............. 11x-8x = -6................... 3x= -6 x = -2
The equation -30 times -10 plus 11X equals -29. This is a math problem.
but crack
If 6x + 10 = 11x , then x=2.
-3x + 6 + 15x =11x + 8 ie -3x + 15x - 11x = 8 - 6 ie x = 2
x=7
5x + 32 = 11x - 105x - 11x = -10 - 32-6x = -42x = 7
x = 8
2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3